Study of electronic structures and absorption bands of BaMgF4 crystal with F colour centre - Kang, L.; Liu, T.; Zhang, Q.; Xu, L.; Zhang, Feiwu (IOP PUBLISHING LTD, 2011)
The electronic structures of BaMgF4 crystals containing an F colour centre are studied within the framework of the fully relativistic self-consistent Direc-Slater theory, using a numerically discrete variational (DV-Xa) method. It is concluded from the calculated results that the energy levels of the F colour centre are located in the forbidden band. The optical transition energy from the ground state to the excited state for the F colour centre is about 5.12 eV, which corresponds to the 242-nm absorption band. These calculated results can explain the origin of the absorption bands.